2021
DOI: 10.3389/fsoc.2021.615232
|View full text |Cite
|
Sign up to set email alerts
|

Practicing Social Isolation During a Pandemic in Brazil: A Description of Psychosocial Characteristics and Traits of Personality During COVID-19 Lockout

Abstract: The experience of the pandemic caused by the Coronavirus and the consequent disease triggered by it (COVID-19) brought to light fragilities that have been long overlooked by the scientific community and by various political and social institutions. The pandemic also brought to the fore certain social practices resulting from individual behaviors, such as wearing a mask and practicing social isolation. It demonstrated the need for social commitment and pro-social behaviors if societies are to respond successful… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
1
0
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 36 publications
0
1
0
3
Order By: Relevance
“…Quando tomados os resultados das análises de diferenças de médias, foi possível identificar a presença de maior ansiedade e estresse estatisticamente significativa nas participantes do sexo feminino. Este dado é coerente com os estudos realizados quanto a diferenças de experiência de sofrimento mental entre homens e mulheres (Lipp & Lipp, 2020;Zanini et al, 2021). Psicol.…”
Section: Discussionunclassified
See 1 more Smart Citation
“…Quando tomados os resultados das análises de diferenças de médias, foi possível identificar a presença de maior ansiedade e estresse estatisticamente significativa nas participantes do sexo feminino. Este dado é coerente com os estudos realizados quanto a diferenças de experiência de sofrimento mental entre homens e mulheres (Lipp & Lipp, 2020;Zanini et al, 2021). Psicol.…”
Section: Discussionunclassified
“…As ações de enfrentamento à pandemia também trouxeram impactos para a rotina familiar. Isto porque as indicações de fechamento de creches e escolas e a necessidade do ensino e do trabalho remoto trazem modificações importantes para o convívio social, para o estabelecimento de redes de suporte, e alterações nos papéis familiares (Zanini et al, 2021), assim como implicam alterações relacionadas aos aspectos econômicos e de acesso a serviços . Diante destas questões, pode-se notar que o cenário da pandemia da Covid-19 contribuiu para o agravamento do sofrimento psicológico, elevando a frequência de sintomas de ansiedade, depressão e estresse nos indivíduos (Lipp & Lipp, 2020;Zanon et al, 2020).…”
unclassified
“…Rola sumienności wydaje się być znacząca ze względu na konieczność dostosowania się do zasad bezpieczeństwa i tzw. reżimu sanitarnego, co z kolei pozwala na zmniejszenie poczucia stresu związanego z zagrożeniem zakażenia i zachorowania (Nudelman i in., 2021;Zanini, Peixoto, Andrade, Tramonte, 2021).…”
Section: Osobowościowe Predyktory Dobrostanu Psychicznego W Czasie Pa...unclassified
“…The study conducted on 63 patients with diabetes in Italy amidst isolation reported improvements in metabolic parameters [ 17 ], while a deterioration in the same parameters was observed in India. In Brazil, an initial deterioration was observed after analyzing 24-month data, especially among the patients receiving public services [ 18 ]. The Nordic study group published another extensive review describing the frequency of loneliness being experienced and the emotional status of the patients [ 19 ].…”
Section: Introductionmentioning
confidence: 99%